Examining the factor structure of the Psychological Mindedness Scale in the Japanese population through exploratory and confirmatory factor analyses. (17th January 2014) - Takagishi, Yukihiro; Uji, Masayo; Adachi, Keiichiro
Abstract Psychological mindedness (PM) is a psychological construct that represents the tendency and ability to understand the relationships between thoughts, feelings, and behavior. This study examined the statistical properties, particularly the factor structure, of the Psychological Mindedness Scale (PMS) in a non‐clinical Japanese sample through exploratory and confirmatory factor analysis. The relationship between PMS and depression was also examined for predictive validity. The results suggested that the PMS tested on a Japanese sample contains the following four factors: (a) belief in the benefits of discussing one's problems; (b) access to feelings; (c) openness to new ideas and capacity to change; and (d) interest in the meaning and motivation of own and others' behavior. Whereas the total PM score and Factors 2 and 3 had negative correlations with depression, there was a positive correlation between Factor 4 and depression. The 4‐factor structure of the scale is deemed to be applicable to the Japanese population.